2018
DOI: 10.1093/ndt/gfy026
|View full text |Cite
|
Sign up to set email alerts
|

The utility of trough mycophenolic acid levels for the management of lupus nephritis

Abstract: Trough levels of MPA do not show a strong correlation with AUC. In clinical situations where MPA levels are essential to guide therapy, an AUC0-4 would be a better indicator of the adequacy of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Nevertheless, contrary to the renal transplant recipients due to better kidney function observed in autoimmune diseases [21,22], in a number of PK studies conducted in non-transplant patients a significant correlation between total MPA C 0 and MPA AUC 0-12 was reported (r = 0.545 [23], r = 0.561 [20], r = 0.578 [21], r = 0.643 [2], r = 0.79 [24], r = 0.90 [6], r = 0.94 [22]). The recent retrospective study that evaluated the relationship between total MPA C 0 and AUC 0-4 has also reported significant correlation (r = 0.55) [25]. These findings are consistent with our study since weak but still statistically significant correlation between absolute as well as dose-normalized total C 0 and AUC 0-2 was observed (r = 0.5508 and r = 0.5699, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, contrary to the renal transplant recipients due to better kidney function observed in autoimmune diseases [21,22], in a number of PK studies conducted in non-transplant patients a significant correlation between total MPA C 0 and MPA AUC 0-12 was reported (r = 0.545 [23], r = 0.561 [20], r = 0.578 [21], r = 0.643 [2], r = 0.79 [24], r = 0.90 [6], r = 0.94 [22]). The recent retrospective study that evaluated the relationship between total MPA C 0 and AUC 0-4 has also reported significant correlation (r = 0.55) [25]. These findings are consistent with our study since weak but still statistically significant correlation between absolute as well as dose-normalized total C 0 and AUC 0-2 was observed (r = 0.5508 and r = 0.5699, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Clinical pharmacokinetics show that the mean clinical trough plasma MPA concentration of lupus nephritis female patients who were administered 1500 mg twice a day of oral MMF is 10.6 μM (3.4 mg/L) [ 23 ]. Another clinical study reported that the plasma concentration of MPA at trough in patients with severe lupus nephritis is 7.7 μM (2.47 mg/L) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical concentrations of MPA do not affect the survival of human DC subsets Clinical pharmacokinetics show that the mean clinical trough plasma MPA concentration of lupus nephritis female patients who were administered 1,500 mg twice a day of oral MMF is 10.6 mM (3.4 mg/L) (22). Another clinical study reported that the plasma concentration of MPA at trough in patients with severe lupus nephritis is 7.7 mM (2.47 mg/L) (23).…”
Section: Resultsmentioning
confidence: 99%